Respuesta :

By determining the area of the square, we get [tex]x^{2} +4x = 3.[/tex]

Step-by-step explanation:

Step 1:

The area of a square is given by squaring its side length.

The given squares side length is [tex](x+2)[/tex] cm.

The area of a square [tex]= a^{2} .[/tex] Here a is the side length.

The area of the square is given as 7 cm².

Step 2:

Substituting the value of a in the equation, we get

[tex]7 = (x+2)^{2} = x^{2} + 4x + 4.[/tex]

Taking the x values on one side and the constants on the other side, we get

[tex]x^{2} +4x= 7-4 =3.[/tex]

So [tex]x^{2} +4x = 3.[/tex]

So it has been proved.

ACCESS MORE